Gender indicators of the United Nations Development Programme - Paulina Stachura; Jerzy Śleszyński (Economic and Environmental Studies (E&ES), 2016)
The Human Development Report published by United Nations Development Programme (UNDP) introduced new measures to evaluate progress in reducing poverty and empowering women: Inequality-adjusted Human Development Index (IHDI), Multidimensional Poverty Index (MPI), Gender Inequality Index (GII), Gender Development Index (GDI). In the paper GDI and GII indicators are presented and analysed, what is supplemented with a detailed analysis of the individual components of these indices for Poland. Additionally, this article wants to evaluate reduction of gender inequality in Poland.
Keywords: Q56; J16; 330; Human Development Index; gender; inequality